2012
DOI: 10.7205/milmed-d-12-00075
|View full text |Cite
|
Sign up to set email alerts
|

Clavicle Fractures in the United States Military: Incidence and Characteristics

Abstract: The incidence of clavicle fractures among U.S. military personnel (0.908 per 1,000 person-years) is higher than previous epidemiological reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…However, the incidence rate of clavicle fractures among U.S. military personnel was found to be 0.91 per 1,000 person-years, which is higher than the values of previous epidemiological reports. An explanation for this finding is that the relatively young and active group of military personnel have job-related upper extremity demands [9]. The result in our study showed an incidence rate of clavicle fractures of 0.94 per 1,000 person-years, which is similar to the rate reported in the aforementioned study.…”
Section: Discussionsupporting
confidence: 89%
“…However, the incidence rate of clavicle fractures among U.S. military personnel was found to be 0.91 per 1,000 person-years, which is higher than the values of previous epidemiological reports. An explanation for this finding is that the relatively young and active group of military personnel have job-related upper extremity demands [9]. The result in our study showed an incidence rate of clavicle fractures of 0.94 per 1,000 person-years, which is similar to the rate reported in the aforementioned study.…”
Section: Discussionsupporting
confidence: 89%
“…Clavicle fractures are common orthopedic injuries that occur in a young active population and account for 2.6% of all fractures [1]. They are more common in the military than in the general population, with an incidence of nearly one per 1000 persons annually [2]. Peak incidence is seen in patients in their second decade and decreases with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…Clavicle fractures make up between 2.6% and 10% of all fractures across all sports 3,5,10,13,25,30 and are common skiing and snowboarding injuries. One study at a ski clinic in Taos, New Mexico, found a clavicle fracture rate of 7.1 per 100,000 mountain visits in skiers and snowboarders over the course of 2 winter sports seasons.…”
mentioning
confidence: 99%